Water-splitting photoelectrodes consisting of heterojunctions of carbon nitride with a p-type low bandgap double perovskite oxide. (8th September 2021) - Kumar, Pawan; Mulmi, Suresh; Laishram, Devika; Alam, Kazi M; Thakur, Ujwal K; Thangadurai, Venkataraman; Shankar, Karthik
Abstract: Quinary and senary non-stoichiometric double perovskites such as Ba2 Ca0.66 Nb1.34− x Fe x O6− δ (BCNF) have been utilized for gas sensing, solid oxide fuel cells and thermochemical CO2 reduction. Herein, we examined their potential as narrow bandgap semiconductors for use in solar energy harvesting. A cobalt co-doped BCNF, Ba2 Ca0.66 Nb0.68 Fe0.33 Co0.33 O6− δ (BCNFCo), exhibited an optical absorption edge at ∼800 nm, p -type conduction and a distinct photoresponse up to 640 nm while demonstrating high thermochemical stability. A nanocomposite of BCNFCo and g-C3 N4 (CN) was prepared via a facile solvent-assisted exfoliation/blending approach using dichlorobenzene and glycerol at a moderate temperature. The exfoliation of g-C3 N4 followed by wrapping on perovskite established an effective heterojunction between the materials for charge separation. The conjugated 2D sheets of CN enabled better charge migration resulting in increased photoelectrochemical performance. A blend composed of 40 wt% perovskites and CN performed optimally, whilst achieving a photocurrent density as high as 1.5 mA cm −2 for sunlight-driven water-splitting with a Faradaic efficiency as high as ∼88%.